Combined Effects of Glenohumeral Mobilization, Stretching, and Thoracic Manipulation on Shoulder Internal Rotation Range of Motion - Brian T Swanson; Marissa Hagenbruch; Bernardine Lapaan; Kirill Skipalskiy (North American Sports Medicine Institute, 2024)
# Background/purpose Interventions including posterior glenohumeral mobilizations (PGM), sleeper stretches, and thoracic manipulation are commonly used to address posterior shoulder tightness. The purpose of this study was to assess the effects of adding thoracic manipulation to PGM and sleeper stretches on passive range of motion (PROM), joint mobility, and infraspinatus electromyographic (EMG) activity in shoulders with decreased internal rotation (IR) PROM. # Design Randomized Sequential Intervention Laboratory Study # Methods Forty individuals with clinically significant IR loss attended two study sessions. Participants were randomized to receive five 30 seconds bouts of either grade III PGM or sleeper stretching. Following a seven-day washout period, all participants attended a second session and received a prescriptive supine HVLA manipulation targeting the T3-4 segment, followed by the previously randomized intervention. Outcome measures included internal rotation PROM, horizontal adduction PROM, posterior glenohumeral joint translation assessed via ultrasound imaging, and EMG activity of the infraspinatus during a PGM. All outcome measures were assessed pre- and immediately post-intervention and compared statistically. # Results There were significant within-group, but not between-group, differences for IR and horizontal adduction PROM following a single session of PGM or sleeper stretch. When combined with thoracic manipulation, significantly smaller within session changes of IR PROM were observed for both PGM (mean difference 4.4, p=0.017) and sleeper stretches (mean difference 6.4, p=0.0005). There were no significant between group differences for horizontal adduction PROM, humeral head translation, or EMG activity across all time points. # Discussion Both GH posterior mobilizations and sleeper stretches improved IR and horizontal adduction PROM in a single session. The addition of thoracic manipulation prior to local shoulder interventions resulted in smaller gains of both IR and horizontal adduction ROM. # Level of evidence Level 2